Exploring Science Learning through Arts-based Sketches and Photos: A Transformative Paradigm - Acharya, Kamal Prasad; Acharya, Milan (Orchid Academia Siraha, 2022)
The study reconnoitres arts-based learning by the use of sketches and photos of basic level students and science teachers. It was accompanied in the basic level public schools of Kirtipur municipality of Kathmandu district. The study explores how the use of sketches and photos promotes students science learning and also designs an appropriate strategy for engaged learning. A qualitative research design was used based on the interpretive paradigm in which data are collected through in-depth interviews and focus group discussions. The data were analysed through verbatim and thematic approaches. The study found the use of arts-based learning like sketches and photos helps to learn science that develops creativity and communication. It was also found that science teachers used sketches and photos linked to the prescribed curriculum while teaching and learning science. It is recommended that the application of sketches and photos would be beneficial for science learning. For this, science curricula and textbooks have to incorporate the techniques of arts-based concept learning in the public schools in Nepal.